PEMBERDAYAAN KADER: SIGAP DAN POJOK BERMAIN TINGKATKAN KUNJUNGAN POSYANDU MAYANG WANGI SAMARINDA, KALIMANTAN TIMUR - Julaikhah, Siti; Astuty, Eny Dwy; Debora, Angelita Novia; Suraini, Fiyeri; Disyanataly, Andi; Nuradi, Elaine Keisha Syahputri; Andini, Meylita; Khalisha, Nailah; Nisa, Rizky Khoirun; Marsyanti, Windy; Permana, Lies; Rohmah, Nur; Nurrachmawati, Annisa; Agustini, Rina Tri (Jurnal AbdiMas Nusa Mandiri, 2025)
Posyandu is a village level of health service that plays a role in improving public health, especially maternal and child health. The existence of posyandu makes an easier access for the community to  basic health services without having to travel long distances. However, the implementation of posyandu still faces various challenges, especially in how low the level of community participation is. Community empowerment with “SIGAP (Sosialisasi Gerakan Aktif Posyandu)” and “Play Corner” programs aims to increase infant and toddler visits to Posyandu Mayang Wangi through cadre empowerment and community education. The methods used include problem awareness through Focus Group Discussion (FGD), socialization planning and implementation, and evaluation using pre-test and post-test. This socialization was carried out by posyandu cadres and public health faculty students as facilitators. The socialization provided information on the importance of visiting the posyandu and nutritional problems in toddlers, as well as a "play corner" to attract children. The enthusiasm of the participants in the discussion session and evaluation through pre-test and post-test showed an improvement in knowledge of the participants, which reflected the effectiveness of the socialization presented by the cadres. The provision of a "play corner" also improved the skills and creativity of cadres in creating educational game media from used goods. This activity succeeded in building community awareness and concern for the importance of posyandu, as well as successfully empowering cadres in raising community awareness of maternal and child health.